THE RELATIONSHIP BETWEEN PSYCHOLOGICAL ENTITLEMENT AND PERSONALITY CHARACTERISTICS - Grigoryan, A.K. (Արդի հոգեբանություն, 2019)
The article discusses conditional relationship between psychological entitlement and personality characteristics. We have considered the Big five personality traits; “Dark Triad”, personal self-esteem, relational self-esteem and collective self-esteem as personality characteristics. As a result of the analysis, it has been found out that personal self-esteem has the most predictive value for psychological entitlement, followed by the Narcissism, Machiavellianism, Openness and Neuroticism.